Axial compression behavior and failure mechanism of CFRP-confined circular hollow steel tube short columns: Theoretical and numerical analysis - Jian Chen; Hairong Huang; Yun Zhou; Kan Liu (PLoS ONE, 2025)
Circular hollow steel tubes (CHST) are widely employed as short columns in various infrastructure applications. This study comprehensively investigates the mechanical behavior of CFRP-Confined CHST (CFRP-CHST) short columns under axial compression through theoretical research, finite element analysis, and existing experimental data. New theoretical formulas for calculating the yield and ultimate bearing capacities of CFRP-CHST short columns under axial loading are developed based on continuum mechanics and the limit equilibrium method. The accuracy and reliability of these formulas are validated through comparisons with finite element simulations and experimental results. Theoretical analysis reveals that CFRP provides only a modest enhancement to the yield-bearing capacity of CHST short columns. However, within a certain range of CFRP layers, the ultimate bearing capacity is significantly improved, albeit with limitations. The concept of the CFRP confinement coefficient is introduced to define the effective range in which CFRP reinforcement substantially enhances the bearing capacity of CHST short columns. The mechanisms restricting this enhancement are investigated in detail through experimental data and finite element analysis. This research offers valuable design and analysis methods for the engineering applications of CFRP-CHST short columns.